Underpricing of Initial Public Offerings: A China-India COMPARISON - WANG, JUN (2015)
Underpricing is a well-known phenomenon in the IPOs market, the large magnitudes of it in the China and India have attracted much attention. This study reviews the current literature regarding underpricing IPOs and considers six theories that may explain the IPO underpricing, namely, signaling theory, underwriter reputation theory, winner’s curse theory, uncertainty theory, time-interval theory and industry-specific theory. A sample of 1061 Chinese IPOs and 143 Indian IPOs between 2007 to 2012 are selected to study the relative importance of the six theories in explaining underpricing in both countries, respectively. Comparison was considered between the two groups and evidence suggests winner’s curse is the most important reason for underpricing in both countries. Signaling theory and time-interval theory also have impact on them, but underwriter reputation is not empirically supported in the Chinese market during the sample period, while uncertainty theory and industry-specific theory seems to be irrelevant in explain underpricing in Indian stock market.